The Beneficial Effects of UM206 on Wound Healing After Myocardial Infarction in Mice Are Lost in Follow-Up Experiments - Daskalopoulos, Evangelos P.; Hermans, Kevin C. M.; Debets, Jacques; Strzelecka, Agnieszka; Leenders, Peter; Vervoort-Peters, Lily; Janssen, Ben J. A.; Blankesteijn, W. Matthijs (Frontiers in Cardiovascular Medicine, 2019)
Introduction: An inadequate wound healing following myocardial infarction (MI) is one of the main etiologies of heart failure (HF) development. Interventions aiming at improving this process may contribute to preserving cardiac function after MI. Our group, as well as others, have demonstrated the crucial role of Wnt/frizzled signaling in post-MI remodeling. In this overview, we compared eight different studies in which we investigated the effects of administration of a peptide fragment of Wnt5a, UM206, on infarct healing in a mouse MI model. Methods: Mice were subjected to permanent left coronary artery ligation, and treated with saline (control) or UM206, administered via osmotic minipumps. Cardiac function was assessed by echocardiography and hemodynamic measurements, while infarct size and myofibroblast content were characterized by (immuno)histochemistry. Results: In the first two studies, UM206 treatment yielded beneficial effects on cardiac dimensions, ejection fraction and lung weight. However, in the following studies no differences between UM206- and control-treated mice were detected for these parameters. Variations in dose of UM206, its manufacturer and genetic background of the mice could not restore the phenotype. An in-depth analysis of the data sets revealed that the absence of effect of UM206 coincided with a lack of adverse cardiac remodeling and HF development in all experimental groups. This change in phenotype of the MI model appeared to coincide with a transition of the housing of the mice from open cages to individually ventilated cages (IVC). This was likely to result in a lower exposure to inflammatory stimuli, because the exchange of micro-organisms between the cages and the environment was eliminated. Discussion: There is increasing evidence that low-grade inflammation strongly determines the outcome of many cardiovascular diseases, including MI. Therefore, the change in housing conditions most likely explains the loss of the HF phenotype after MI, thereby eliminating the potential for UM206 to show its beneficial effect on adverse cardiac remodeling. This conclusion is further supported by the beneficial effects observed for UM206 in a swine model of ischemia/reperfusion where the animals were housed under traditional housing conditions, and reports from others showing beneficial effects of Wnt inhibition in infarct healing.